2019
DOI: 10.1038/s41398-019-0553-z
|View full text |Cite|
|
Sign up to set email alerts
|

The selective orexin-2 antagonist seltorexant (JNJ-42847922/MIN-202) shows antidepressant and sleep-promoting effects in patients with major depressive disorder

Abstract: Excessive arousal has a role in the pathophysiology of major depressive disorder (MDD). Seltorexant (JNJ-42847922/MIN-202) is a selective antagonist of the human orexin-2 receptor (OX2R) that may normalize excessive arousal and thereby attenuate depressive symptoms. In this study, the effects of night-time arousal suppression on depressive symptoms were investigated. 47 MDD patients with a total Inventory of Depressive Symptomatology (IDS) score of ≥30 at screening were included in a randomized, double-blind, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 49 publications
2
40
0
Order By: Relevance
“…However, some clinical studies have reported contradictory results of OxR2. Seltorexant (JNJ-42847922/MIN-202), an OxR2 antagonist, was reported to induce antidepressant effects in clinical patients ( Brooks et al, 2019 ; Recourt et al, 2019 ). It is noteworthy that patients enrolled in these clinical trials with MDD were likely to be very different from animal models of CSDS in terms of brain states and mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some clinical studies have reported contradictory results of OxR2. Seltorexant (JNJ-42847922/MIN-202), an OxR2 antagonist, was reported to induce antidepressant effects in clinical patients ( Brooks et al, 2019 ; Recourt et al, 2019 ). It is noteworthy that patients enrolled in these clinical trials with MDD were likely to be very different from animal models of CSDS in terms of brain states and mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Mice treated with chronic mild stress (CMS) showed an increased percentage of Fos-positive orexinergic neurons in the PeF/LHA ( Nollet et al, 2011 ). Multiple reports have also emphasized the regulatory role of OxR2 in depressive-like behaviors in animals ( Arendt et al, 2014 ; Scott et al, 2011 ; Staton et al, 2018 ) and MDD in human trials ( Brooks et al, 2019 ; De Boer et al, 2018 ; Recourt et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“… 147 , 148 Seltorexant (JNJ-42847922) is an OX2R antagonist currently in phase 3 clinical development for the treatment of insomnia and major depressive disorder. 149 A phase 2b active- and placebo-controlled study in adult and elderly subjects with insomnia disorder found that seltorexant at 5, 10 and 20 mg significantly improved LPS versus placebo. 150 Greater improvement in LPS was also seen with seltorexant 20 mg compared with zolpidem.…”
Section: Introductionmentioning
confidence: 99%
“…Seltorexant, a potent and highly selective antagonist of orexin-2 receptor, is being developed as a treatment for MDD due to its potential role in normalizing sleep ( Bonaventure et al, 2015 ). In exploratory clinical studies, seltorexant displayed antidepressant effects by improving core symptoms of depression in patients with MDD regardless of sleep impairment and improved sleep efficiency in patients with insomnia ( Brooks et al, 2019 ; Recourt et al, 2019 ). The present study investigated the antidepressant effects, safety, and tolerability of various doses of seltorexant as adjunctive therapy in patients with MDD who had experienced inadequate response to the current antidepressant therapy.…”
Section: Introductionmentioning
confidence: 99%